Quality and Antioxidant Activity of Buckwheat-Based Cookies Designed for a Raw Food Vegan Diet as Affected by Moderate Drying Temperature - Brožková, Iveta; Dvořáková, Veronika; Michálková, Kateřina; Červenka, Libor; Velichová, Helena (Plant foods for human nutrition (Dordrecht, Netherlands), 2016)
Buckwheat cookies with various ingredients for raw food vegan diet are usually prepared by soaking them in water at ambient temperature followed by drying at moderate temperature. The aim of this study was to examine the temperature effect on the microbiological quality, antioxidant properties and oxidative stability of lipids of final dried samples. The mixture of ingredients was soaked for 20 h in distilled water, and then cookies were formed and dried in air-forced oven at constant temperature in the range from 40 to 60 °C. Total viable counts, fungi, yeasts, coliform and aerobic spore-forming bacteria counts were evaluated in dried samples and were found to decrease during drying at 50 and 60 °C. Antioxidant activity was determined by DPPH and ABTS assays, and the former showed the highest value at 40 °C. Superoxide dismutase activity was also higher at 40 °C in comparison with that at 60 °C. The percentage of lipid peroxidation inhibition increased with the increase in drying temperature until 4th day of incubation. While peroxide value was significantly higher in samples dried at 40 °C, TBARS values did not show significant changes during the drying process. The results of this study suggest that drying buckwheat-based cookies at 40 °C retained their good antioxidant properties but represent a potentially serious microbial hazard.
Keywords: syrová strava; antioxidancia; Lipid Peroxidation; Desiccation; Antioxidant; vysoušení; Fagopyrum; superoxiddismutasa; Raw Foods; bakteriální nálož; látky reagující s kyselinou thiobarbiturovou; peroxidace lipidů; voda; Bacterial Load; Diet, Vegan; Food Contamination; dieta veganská; Antioxidants; kontaminace potravin; Thiobarbituric Acid Reactive Substances; Drying process; Water; Raw food; Microbial risk; potravinářská mikrobiologie; Food Microbiology; Lipid peroxidation; manipulace s potravinami; Food Handling; Temperature; Superoxide Dismutase; teplota